2018
DOI: 10.3920/wmj2017.2283
|View full text |Cite
|
Sign up to set email alerts
|

Advances in molecular and genomic research to safeguard food and feed supply from aflatoxin contamination

Abstract: Worldwide recognition that aflatoxin contamination of agricultural commodities by the fungus Aspergillus flavus is a global problem has significantly benefitted from global collaboration for understanding the contaminating fungus, as well as for developing and implementing solutions against the contamination. The effort to address this serious food and feed safety issue has led to a detailed understanding of the taxonomy, ecology, physiology, genomics and evolution of A. flavus, as well as strategies to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 235 publications
(262 reference statements)
0
12
0
Order By: Relevance
“…Once the fungus has colonized the crop it can survive in the field under harsh conditions for several years by forming resistant structures termed sclerotia (Horn et al , 2014). Upon colonization of the plant, A. flavus produces a number of mycotoxins, including the highly carcinogenic family of toxins known as aflatoxins (Bhatnagar et al , 2018). Contaminated crops are often destroyed or significantly reduced in value leading to substantial economic losses in the range of one billion US dollars annually during years of severe aflatoxin outbreaks (Robens & Cardwell 2003, & Wu et al 2008).…”
mentioning
confidence: 99%
“…Once the fungus has colonized the crop it can survive in the field under harsh conditions for several years by forming resistant structures termed sclerotia (Horn et al , 2014). Upon colonization of the plant, A. flavus produces a number of mycotoxins, including the highly carcinogenic family of toxins known as aflatoxins (Bhatnagar et al , 2018). Contaminated crops are often destroyed or significantly reduced in value leading to substantial economic losses in the range of one billion US dollars annually during years of severe aflatoxin outbreaks (Robens & Cardwell 2003, & Wu et al 2008).…”
mentioning
confidence: 99%
“…The gene aflS is located adjacent to aflR, and there is no significant similarity between its putative product and any other proteins found in databases. The gene aflS is clearly involved in aflatoxin regulation since deletion mutants do not produce aflatoxins and the levels of expression of some genes of the aflatoxin pathway are significantly reduced (Yu and Ehrlich 2011;Bhatnagar et al 2018). Chang (2003) suggested that aflS might be modulating aflatoxin biosynthesis by interacting with aflR although the exact role of aflS has not yet been made clear (Bhatnagar et al 2018).…”
Section: Aflatoxinsmentioning
confidence: 99%
“…The results showed that isolates which produced higher levels of aflatoxin exhibited fewer differentially expressed genes in increased stress conditions. Thus, secondary metabolites including aflatoxins may be produced as a response to the oxidative stress conditions [ 130 ]. For Ochratoxin, a recent review of transcriptomic studies indicated that the transcriptomic studies carried out do not clarify the modes of action of OTA but have contributed to relevant toxicological information.…”
Section: Transcriptomics Approachmentioning
confidence: 99%